Improving the Ability of Higher Order Thinking Skills through Information Technology Media in Civic Education Learning - Pebriyenni; M. Nursi; Muslim (Universitas Jambi, Indonesia, 2022)
This research aimed to prove how the Civic education learning process in high school that uses information technology media can increase the ability of higher order thinking skills. Additionally, this research is experimental research that involved manipulating independent variables, controlling external variables, and measuring the effects of independent variables on the dependent variable. There were 20 students for the higher-order thinking skills data for the control class and 20 students for the experiment class. The average value of students' higher-order thinking skills or mean pre-test for the control class was 74,2500, while for the experiment class was 76,2500. Meanwhile, the post-test mean for the control class was 80,5000, while the experiment class was 84.5000. Thus, statistically descriptive, the conclusion is that there is a difference in the average of higher order thinking skills of students between the control and the experiment class.